A flow analysis of the Irish Live Register - Harrison, Michael J.; Walsh, Patrick Paul (Economic & Social Studies, 1994)
This paper makes use for the first time of data on the flows into and out of the Irish Live Register. It describes the construction of consistent quarterly flow series for the period 1967 to 1993. The analysis suggests that the build-up of the unemployment stock is mainly due to the inflows to the Live Register. The results also suggest that in the 1970s the inflows seem to have been largely determined by market and demographic adjustments in Ireland induced by developments in Britain. In the 1980s, by contrast, the inflows seem to have been driven substantially by demographic developments in Ireland.
Keywords: Unemployment; Live Register; Demography; Ireland; Labour force